Looking beyond year 1 in the molecular era of pediatric brain tumor diagnosis: confirmatory testing of germline variants found on tumor sequencing - Greene, Brittany L.; Stasi, Shannon M.; Ting, Michelle A.; Waligorski, Natalie; Cole, Bonnie L.; Lockwood, Christina M.; Paulson, Vera A.; Buchan, Jillian G.; Lee, Amy; Ojemann, Jeffrey G.; Ellenbogen, Richard G.; Stevens, Jeffrey; et al. (Frontiers in Oncology, 2024)
Purpose: Somatic molecular profiling of pediatric brain tumors aids with the diagnosis and treatment of patients with a variety of high-and low-grade central nervous system neoplasms. Here, we report follow-up targeted germline evaluation for patients with possible germline variants following tumor only testing in the initial year in which somatic molecular testing was implemented at a single institution.Patients and Methods: Somatic testing was completed for all tumors of the central nervous system (CNS) undergoing diagnostic workup at Seattle Children's Hospital during the study period of November 2015 to November 2016. Sequencing was performed in a College of American Pathologists-accredited, Clinical Laboratory Improvements Amendments-certified laboratory using UW-OncoPlex TM assay (version 5), a DNA-based targeted next generation sequencing panel validated to detect genetic alterations in 262 cancer-related genes. We tracked subsequent clinical evaluation and testing on a subgroup of this cohort found to have potential germline variants of interest. Results: Molecular sequencing of 88 patients' tumors identified 31 patients with variants that warranted consideration of germline testing. To date, 19 (61%) patients have been tested. Testing confirmed germline variants for ten patients (31% of those identified for testing), one with two germline variants (NF1 and mosaic TP53). Eight (26%) patients died before germline testing was sent. One patient (13%) has not yet had testing. Conclusion: Clinically validated molecular profiling of pediatric brain tumors identifies patients who warrant further germline evaluation. Despite this, only a subset of these patients underwent the indicated confirmatory sequencing. Further work is needed to identify barriers and facilitators to this testing, including the role of genetic counseling and consideration of upfront paired somatic-germline testing. Deleted: Further, the criteria used by the molecular tumor board to 254 determine whether a patient's tumor sequencing results warranted 255 germline testing included both objective criteria, such as family 256 history, and professional experience.